1970
DOI: 10.1002/jcp.1040750103
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of protoplasm. IV. Cinematographic analysis of the contraction of some peritrichs

Abstract: The contraction and relaxation of Vorticella dificilis, V . campanula and Carchesium sp. were studied by high speed cinematography. In Vorticella it was shown that coiling of the stalk usually started near the zooid and spread downwards; the point of initiation bore no relation to the position of the stimulating electrodes. Contraction took about 5 msec to complete, and the fully contracted animals were 2 9 1 3.9% of their original lengths. The zooids were 6 6 2 5.0% and the stalks 14?6.0%of their original len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 11 publications
1
20
1
Order By: Relevance
“…Their experiment was, in other words, quite different from ours. Amos [1975] calculated the minimum spasmoneme tension value from the high speed film data of Jones et al [1970]. When Vorticellu contracts, the zooid, which may be approximated to a sphere of radius 20 bm, may be pulled 80 pm…”
Section: Maximum Isometric Tensionmentioning
confidence: 99%
“…Their experiment was, in other words, quite different from ours. Amos [1975] calculated the minimum spasmoneme tension value from the high speed film data of Jones et al [1970]. When Vorticellu contracts, the zooid, which may be approximated to a sphere of radius 20 bm, may be pulled 80 pm…”
Section: Maximum Isometric Tensionmentioning
confidence: 99%
“…When the concentration of free calcium ion is raised from to M, the filaments reversibly bind calcium contracting to less than one third of their initial length. The maximum contraction rate of 200 lengths s-I (Jones et al 1970;Amos et al 1975) is almost an order of magnitude faster than that reported for muscle (Close 1965) and the tension of up to 80 kN m-2 (Rahat et al 1973) is comparable to that developed by vertebrate striated muscle, 50 to 400 kN mP2 (Wilkie 1954). The contraction of this organelle depends on the calcium concentration.…”
Section: Introductionmentioning
confidence: 79%
“…Contraction begins at the body and travels down the stalk. 5 Therefore the part of the stalk nearest the zooid is the first to receive the strongest force before breakage of other parts can arise. Figure 5 shows a decrease in stalk contractions as loading flow increases.…”
Section: Deformation and Breakage Of V Convallariamentioning
confidence: 99%
“…The maximum isometric tension of Vorticella convallaria is 4 ϫ 10 −8 N. For live cell measurement, high speed video acquisition is the primary means of characterizing the contraction because the rapid movement of Vorticella is not readily amenable to other methods of study. 5,7,8 Jones et al 5 obtained high speed images of Vorticella difficilis and measured its contraction speed and length change. Moriyama et al 7 estimated the maximum tension as 5.58ϫ 10 −8 N. Upadhyaya et al 8 measured contraction dynamics such as speed, force, and energy of live Vorticella in various viscous solutions.…”
mentioning
confidence: 99%